Induced Abortion by Vaginal Use of Aluminum Phosphide in a 44-Year-Old Woman: A Case Report - Khalighi, Zahra; Hashemi, Fatemeh-Sadat; Bazgir, Nasrin; Azami, Golnaz; Shafiei, Elham (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Aluminum phosphide (AlP) is an efficient and toxic pesticide that is easily available in many Asian countries such as Iran. Many cases of unintentional or suicidal use of AlP have been reported in these countries, and these statistics are rising rapidly. We aim to present a case of abortion induced by vaginal use of AlP. We report a 44-year-old gravid woman who self-administered one-quarter of a 3-g AlP tablet intravaginally. Ultrasound at 6 hours post-admission showed no fetal movement or heart motion. Intravaginal administration of AlP can lead to fetal death and abortion. There is concern about the spread of vaginal use of these agents in pregnant women, as the number of illegal abortions is increasing.